Oleanane-type saponins and prosapogenins from Albizia julibrissin and their cytotoxic activities. (May 2021) - Han, Qinghua; Qian, Yi; Wang, Xuda; Zhang, Qingying; Cui, Jingrong; Tu, Pengfei; Liang, Hong
Abstract: Two undescribed oleanane-type saponins, julibrosides K–L, along with three undescribed oleanane-type prosapogenins, julibrosides M–O, were isolated from the stem bark of Albizia julibrissin Durazz. and the mild alkaline hydrolysate of the total saponin, respectively . Their structures were established by extensive analysis of 1D and 2D NMR experiments (COSY, TOCSY, HSQC, HMBC, and HSQC-TOCSY) and mass spectrometry. Furthermore, the cytotoxic activities of the isolated compounds against BGC-823, A549, HCT-116, and HepG2 cell lines were evaluated, and julibroside L showed significant cytotoxic activities against the four cancer cell lines with IC50 values of 5.77, 4.80, 4.26, and 4.93  μ M, respectively. Graphical abstract: Five undescribed oleanane-type saponins, julibrosides K–O were isolated from the stem bark of Albizia julibrissin Durazz. Julibroside L showed significant cytotoxic activities against several cancer cell lines. Image 1 Highlights: Five undescribed oleanane-type saponins, julibrosides K–O, were isolated from the stem bark of Albizia julibrissin . Julibroside L showed significant cytotoxic activities against BGC-823, A549, HCT-116, and HepG2 cell lines.